At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
[tex]\hbox{Domain:}\\
x^2+x-2\geq0 \wedge x^2-4x+3\geq0 \wedge x^2-1\geq0\\
x^2-x+2x-2\geq0 \wedge x^2-x-3x+3\geq0 \wedge x^2\geq1\\
x(x-1)+2(x-1)\geq 0 \wedge x(x-1)-3(x-1)\geq0 \wedge (x\geq 1 \vee x\leq-1)\\
(x+2)(x-1)\geq0 \wedge (x-3)(x-1)\geq0\wedge x\in(-\infty,-1\rangle\cup\langle1,\infty)\\
x\in(-\infty,-2\rangle\cup\langle1,\infty) \wedge x\in(-\infty,1\rangle \cup\langle3,\infty) \wedge x\in(-\infty,-1\rangle\cup\langle1,\infty)\\
x\in(-\infty,-2\rangle\cup\langle3,\infty)[/tex]
[tex] \sqrt{x^2+x-2}+\sqrt{x^2-4x+3}=\sqrt{x^2-1}\\ x^2-1=x^2+x-2+2\sqrt{(x^2+x-2)(x^2-4x+3)}+x^2-4x+3\\ 2\sqrt{(x^2+x-2)(x^2-4x+3)}=-x^2+3x-2\\ \sqrt{(x^2+x-2)(x^2-4x+3)}=\dfrac{-x^2+3x-2}{2}\\ (x^2+x-2)(x^2-4x+3)=\left(\dfrac{-x^2+3x-2}{2}\right)^2\\ (x+2)(x-1)(x-3)(x-1)=\left(\dfrac{-x^2+x+2x-2}{2}\right)^2\\ (x+2)(x-3)(x-1)^2=\left(\dfrac{-x(x-1)+2(x-1)}{2}\right)^2\\ (x+2)(x-3)(x-1)^2=\left(\dfrac{-(x-2)(x-1)}{2}\right)^2\\ (x+2)(x-3)(x-1)^2=\dfrac{(x-2)^2(x-1)^2}{4}\\ 4(x+2)(x-3)(x-1)^2=(x-2)^2(x-1)^2\\[/tex]
[tex] 4(x+2)(x-3)(x-1)^2-(x-2)^2(x-1)^2=0\\ (x-1)^2(4(x+2)(x-3)-(x-2)^2)=0\\ (x-1)^2(4(x^2-3x+2x-6)-(x^2-4x+4))=0\\ (x-1)^2(4x^2-4x-24-x^2+4x-4)=0\\ (x-1)^2(3x^2-28)=0\\ x-1=0 \vee 3x^2-28=0\\ x=1 \vee 3x^2=28\\ x=1 \vee x^2=\dfrac{28}{3}\\ x=1 \vee x=\sqrt{\dfrac{28}{3}} \vee x=-\sqrt{\dfrac{28}{3}}\\[/tex]
There's one more condition I forgot about
[tex]-(x-2)(x-1)\geq0\\ x\in\langle1,2\rangle\\[/tex]
Finally
[tex]x\in(-\infty,-2\rangle\cup\langle3,\infty) \wedge x\in\langle1,2\rangle \wedge x=\{1,\sqrt{\dfrac{28}{3}}, -\sqrt{\dfrac{28}{3}}\}\\ \boxed{\boxed{x=1}}[/tex]
[tex] \sqrt{x^2+x-2}+\sqrt{x^2-4x+3}=\sqrt{x^2-1}\\ x^2-1=x^2+x-2+2\sqrt{(x^2+x-2)(x^2-4x+3)}+x^2-4x+3\\ 2\sqrt{(x^2+x-2)(x^2-4x+3)}=-x^2+3x-2\\ \sqrt{(x^2+x-2)(x^2-4x+3)}=\dfrac{-x^2+3x-2}{2}\\ (x^2+x-2)(x^2-4x+3)=\left(\dfrac{-x^2+3x-2}{2}\right)^2\\ (x+2)(x-1)(x-3)(x-1)=\left(\dfrac{-x^2+x+2x-2}{2}\right)^2\\ (x+2)(x-3)(x-1)^2=\left(\dfrac{-x(x-1)+2(x-1)}{2}\right)^2\\ (x+2)(x-3)(x-1)^2=\left(\dfrac{-(x-2)(x-1)}{2}\right)^2\\ (x+2)(x-3)(x-1)^2=\dfrac{(x-2)^2(x-1)^2}{4}\\ 4(x+2)(x-3)(x-1)^2=(x-2)^2(x-1)^2\\[/tex]
[tex] 4(x+2)(x-3)(x-1)^2-(x-2)^2(x-1)^2=0\\ (x-1)^2(4(x+2)(x-3)-(x-2)^2)=0\\ (x-1)^2(4(x^2-3x+2x-6)-(x^2-4x+4))=0\\ (x-1)^2(4x^2-4x-24-x^2+4x-4)=0\\ (x-1)^2(3x^2-28)=0\\ x-1=0 \vee 3x^2-28=0\\ x=1 \vee 3x^2=28\\ x=1 \vee x^2=\dfrac{28}{3}\\ x=1 \vee x=\sqrt{\dfrac{28}{3}} \vee x=-\sqrt{\dfrac{28}{3}}\\[/tex]
There's one more condition I forgot about
[tex]-(x-2)(x-1)\geq0\\ x\in\langle1,2\rangle\\[/tex]
Finally
[tex]x\in(-\infty,-2\rangle\cup\langle3,\infty) \wedge x\in\langle1,2\rangle \wedge x=\{1,\sqrt{\dfrac{28}{3}}, -\sqrt{\dfrac{28}{3}}\}\\ \boxed{\boxed{x=1}}[/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.